(untitled) (Plant Tissue Culture and Biotechnology, 2010)
High frequency of calli was obtained from leaf and spadix segments of Anthurium andraeanum L. when cultured on N6 medium containing 2.5 mg/l BAP and 0.2 mg/l 2,4-D in dark condition. The calli were maintained in dark condition on the same medium containing same hormonal supplements by sub-culturing up to three months but no shoot formation occurred during this period. Leaf and spadix segments derived calli were then tried for multiple shoot regeneration by culturing onto MS fortified with BAP and Kn singly or in combination with NAA in light condition. Best response towards multiple shoot regeneration was observed from both leaf and spadix segments derived calli on MS fortified with 1.0 mg/l BAP. In this combination an average of 18 shoot buds regenerated from leaf segment derived callus while 14 shoot buds regenerated from spadix segment derived callus. The number of shoot buds increased three to four-folds after subculturing in the same medium. Regenerated multiple shoots were excised and cultured onto half strength of MS with different concentrations of IBA and IAA for root induction. Best root development was obtained in half strength MS containing 1.0 mg/l IBA. About 85 per cent of the regenerated plantlets survived in natural conditions. Key words: Clonal propagation, In vitro, Anthurium andraeanum D.O.I. 10.3329/ptcb.v19i1.4961 Plant Tissue Cult. & Biotech. 19(1): 61-69, 2009 (June)